Palynology from the Cenomanian Mata Amarilla Formation, southern Patagonia, Argentina - Santamarina, Patricio Emmanuel; Barreda, Viviana Dora; Iglesias, Ari; Varela, Augusto Nicolás (Cretaceous Research)
The critical climatic changes that occurred during the Albian–Turonian Cretaceous interval led to a major biotic turnover, both in terrestrial and marine ecosystems. Several large-scale palynological works have been conducted in the Northern Hemisphere, but information for the Southern Hemisphere remains scarce. Particularly for southern South America, there are only a few palynological works focused on this important time interval. We report here, a diverse palynoflora recovered from the Cenomanian Mata Amarilla Formation, southern Patagonia, Argentina. The palynological assemblage is composed of 64 species within 47 genera. Three new species are here defined: Polycingulatisporites multiverrucata sp. nov., Clavatisporites cenomaniana sp. nov. and Collarisporites minor sp. nov., and 18 species are first recorded for southern South America. Cluster analysis including several Albian–Turonian palynofloras of middle and high latitudes of eastern and western Gondwana show that Patagonian palynofloras are clustered together, sharing a great compositional similarity, but with features common to those of the Antarctic Peninsula and New Zealand. The Mata Amarilla Formation palynofloras here presented show characteristics of the Cyclusphaera psilata-Classopollis Sub-province, extending its stratigraphic range into the Cenomanian. This palynoflora fits well with the evolutionary scheme of angiosperms previously proposed for Argentina, and adds a new characteristic taxon (cf. Dichastopollenites sp.). The presence of Albian–Cenomanian megaspore species (Arcellites disciformis and Balmeisporites sp. cf. B. holodictyus), the abundance of common elements of the Early Cretaceous Patagonian assemblages (e.g. Classopollis and Cyclusphaera), and the relative scarcity of angiosperm pollen grains support a Cenomanian age for the Mata Amarilla Formation. Fil: Santamarina, Patricio Emmanuel. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de ...